Identifying a disease-specific renin–angiotensin–aldosterone system fingerprint in patients with primary adrenal insufficiency. Issue 1 (July 2019) - Wolf, Peter; Mayr, Johanna; Beiglböck, Hannes; Fellinger, Paul; Winhofer, Yvonne; Poglitsch, Marko; Gessl, Alois; Kautzky-Willer, Alexandra; Luger, Anton; Krebs, Michael
Abstract : Background: In patients suffering from primary adrenal insufficiency (AI) mortality is increased despite adequate glucocorticoid (GC) and mineralocorticoid (MC) replacement therapy, mainly due to an increased cardiovascular risk. Since activation of the renin–angiotensin–aldosterone system (RAAS) plays an important role in the modulation of cardiovascular risk factors, we performed in-depth characterization of the RAAS activity. Methods: Eight patients with primary AI (female = 5; age: 56 ± 21 years; BMI: 22.8 ± 2 kg/m 2 ; mean blood pressure: 140/83 mmHg; hydrocortisone dose: 21.9 ± 5 mg/day; fludrocortisone dose: 0.061 ± 0.03 mg/day) and eight matched healthy volunteers (female = 5; age: 52 ± 21 years; BMI: 25.2 ± 4 kg/m 2 ; mean blood pressure:135/84 mmHg) were included in a cross-sectional case–control study. Angiotensin metabolite profiles (RAS-fingerprints) were performed by liquid chromatography mass spectrometry. Results: In patients suffering from primary AI, RAAS activity was highly increased with elevated concentrations of renin concentration ( P = 0.027), angiotensin (Ang) I ( P = 0.022), Ang II ( P = 0.032), Ang 1-7 and Ang 1-5. As expected, aldosterone was not detectable in the majority of AI patients, resulting in a profoundly suppressed aldosterone-to-AngII ratio (AA2 ratio, P = 0.003) compared to controls. PRA-S, the angiotensin-based marker for plasma renin activity, correlated with plasma renin activity ( r = 0.983; P < 0.01) and plasma renin concentration ( r = 0.985; P < 0.001) and was significantly increased in AI patients. Conclusions: AI is associated with a unique RAAS profile characterized by the absence of aldosterone despite strongly elevated levels of angiotensin metabolites, including the potent vasoconstrictor AngII. Despite state-of-the-art hormone replacement therapy, the RAAS remains hyperactivated. The contribution of Ang II in cardiovascular diseases in AI patients as well as a potential role for providing useful complementary information at diagnosis and follow up of AI should be investigated in future trials.